Subdural Pneumocephalus Aspiration Reduces Recurrence of Chronic Subdural Hematoma. Issue 4 (17th July 2019) - Chavakula, Vamsidhar; Yan, Sandra C; Huang, Kevin T; Liu, Jingyi; Bi, Wenya Linda; Rozman, Peter; Chi, John H
Abstract: BACKGROUND: Chronic subdural hematoma (cSDH) is a common neurosurgical condition, with symptoms ranging from headaches to coma. Operative evacuation is the treatment of choice. Subdural reaccumulation leading to reoperation is a vexing postoperative complication. OBJECTIVE: To present a novel technique for intraoperative aspiration of pneumocephalus via a subdural drain following SDH evacuation as a method of reducing potential subdural space and promoting cerebral expansion, thereby decreasing SDH recurrence. METHODS: In this retrospective study, 15 patients who underwent operative evacuation of cSDH between 2008 and 2015 were assessed. Six patients underwent a small craniotomy with intraoperative pneumocephalus aspiration. These patients were matched by age, gender, and anticoagulation status to 9 patients who underwent evacuation of SDH without pneumocephalus aspiration. Quantitative volumetric analysis was performed on the preoperative, postoperative, and 1-mo follow-up computed tomography scan to assess the subdural volume. RESULTS: In the immediate postoperative period, there was no difference in the percentage of residual subdural fluid between the aspiration and control groups (0.291 vs 0.251; P = 1.00). There was a decrease in amount of pneumocephalus present when the aspiration technique was applied (0.182 vs 0.386; P = .041). At 1-mo follow-up, there was a decrease in the residual cSDH volume between the aspiration and the control groups (28.7 mL vs 60.8 mL; P = .011). The long-term evacuation rate was greater in the aspiration group (75.4% vs 51.6%; P = .015). CONCLUSION: Intraoperative aspiration of cSDH cavity is a safe technique that may enhance cerebral expansion and reduce likelihood of cSDH recurrence.